PENERAPAN MODEL WATERFALL PADA PENGEMBANGAN SISTEM INFORMASI REKAM MEDIS KLINIK RAWAT INAP NAJA SHAFANA PURWOKERTO - Rahmawati, Eka; Wijianto, Ragil (LPPM Universitas Nusa Mandiri, 2019)
Computer is the one of technology that can make people activity easier. To maximize the computer utilization it need a computerization system. Like on Klinik Pratama Rawat Inap Naja Shafana that give health service. The service that given are outpatient, inpatient and emergency unit. Until now, medical records procedure at Klinik Pratama Rawat Inap Naja Shafana still done by hand, one of them is on outpatient procedure. The registration of medical patient data was written on paper that susceptible from damage and data loss. Besides that, the history of medical patient start form anamnesia, diagnose and therapy wrote on paper too. The Medical patient checkup data of inpatient still on a paper. The data have been random archived, so it need long time for searching data and arrange the report. As a health unit that serve general society, Klinik Pratama Rawat Inap Naja Shafana need an information system that can accelerate performance and increase redundancy, data loss and data detriment. The information system also can make archived and data searched easily and can block access from uncompetent people. Therefore, it’s necessary to make medical records information system on Klinik Pratama Rawat Inap Naja Shafana. A computerization system besides accelerate performance also can make data reporting easier.